Pengaruh Trend Tiktok Velocity Terhadap Perubahan Komunikasi Budaya Anggota HIMAKOM UBSI Kaliabang dan Cut Mutia Bekasi - Rizkia Maulidina Citra Kartika; Allifia Cahyani Junaedi; Arsya Azikra; Farrel Rayandra J; Fadly Alfarizi R; Fidila Rika Aniqoh; Grisselda Sekar Herdayani; Maharani Savitri; Mumtaz Ziaulhaq Hidayatullah; Nanda Arya Widi Pratama; Ruth Destini Simorangkir; Sheila Aulia Palma; Setyawan Djoti; Zaidan Syauqillah; Isa Wijayanti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine the influence of the TikTok Velocity trend on the changes in cultural communication among members of the Communication Science Student Association (HIMAKOM) at Universitas Bina Sarana Informatika (UBSI) Kaliabang and Cut Mutia campuses. TikTok Velocity is a popular visual trend among students, characterized by fast-cut motion effects used to express personal identity through short videos. The research adopts a quantitative approach using a descriptive-correlational method. The sample consists of 33 respondents selected from a population of 48 active HIMAKOM members using simple random sampling. Data collection was conducted through questionnaires with a Likert scale and analyzed using validity and reliability tests, Pearson correlation, and t-test. The results show a significant influence between the TikTok Velocity trend and changes in cultural communication, with a correlation coefficient of 0.992 and a significance value of p < 0.001. Most respondents demonstrated high involvement in the velocity trend and acknowledged a shift in their communication style towards more visual, expressive, and symbolic forms. Theoretical frameworks used include the Diffusion of Innovations, Cultural Communication, Uses and Gratification, and New Media Theory. It can be concluded that the TikTok Velocity trend plays a role in shaping new ways for students to interact and convey cultural messages in the digital era.